2011
DOI: 10.1088/0029-5515/51/7/073024
|View full text |Cite
|
Sign up to set email alerts
|

Systematic design of a sawtooth period feedback controller using a Kadomtsev–Porcelli sawtooth model

Abstract: A systematic methodology for structured design of feedback controllers for the sawtooth period is presented, based on dedicated identification of the sawtooth dynamics. Therefore, a combined Kadomtsev–Porcelli model of a sawtoothing plasma actuated by an electron cyclotron current drive system has been set-up. This is used to derive the linearized input–output relations (transfer functions) from the varying deposition location of the electron cyclotron waves (ECW) to the sawtooth period. These transfer functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(97 citation statements)
references
References 31 publications
2
95
0
Order By: Relevance
“…Other possibilities are to estimate the signals noise by use of automatic variance estimators, which are present in most signal processing software. The threshold T min in (12) defines the absolute lower bound on the wavelet coefficients due to noise and (13) determines what the maximum amplitude of the wavelet coefficients due to noise are for every scale.…”
Section: Crash Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other possibilities are to estimate the signals noise by use of automatic variance estimators, which are present in most signal processing software. The threshold T min in (12) defines the absolute lower bound on the wavelet coefficients due to noise and (13) determines what the maximum amplitude of the wavelet coefficients due to noise are for every scale.…”
Section: Crash Detectionmentioning
confidence: 99%
“…Some control experiments and simulations for the sawteeth period have been presented in the literature [3][4][5][10][11][12][13]. Most of the above-mentioned experiments were carried out in open-loop and some in closed-loop, but a systematic optimization of the overall control loops (which includes the sensor) has not been presented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [12], it is shown that the sawtooth period controller is stable for small period sawteeth, and is actually unstable for larger period sawteeth, where the controller introduces heavy oscillations in the launcher angle. This stability problem is addressed in [15], where the dynamics of a sawtooth model with constant plasma parameters is identified in a selected region of the operating range by specifying limits on the launcher angle. A stabilizing linear feedback controller is designed, and the tracking of sawtooth period references is demonstrated.…”
Section: Introductionmentioning
confidence: 99%